Electronic cross section, stopping power and energy-loss straggling of metals for swift protons, alpha particles and electrons - de Vera, Pablo; Abril, Isabel; Garcia-Molina, Rafael (Frontiers in Materials, 2023)
Understanding and quantifying the electronic inelastic interactions of swift ions and electrons in metals is fundamental for many applications of charged particle beams. A common theoretical approach is moreover desirable for the case of both types of projectiles, as large numbers of secondary electrons arise as the result of ion interaction with metals. The electronic cross section, stopping power and energy loss straggling resulting from the interaction of swift protons, alpha particles and electrons when moving through the metals aluminum, iron, copper, molybdenum, platinum and gold, are calculated theoretically for a wide energy range of the projectiles. The model is based on the dielectric formalism, which realistically accounts for the excitation spectrum of each metal through the Mermin Energy Loss Function -- Generalized Oscillator Strength (MELF-GOS) methodology. The impact of the complexity of the excitation spectrum of each metal (encompassing interband transitions and collective excitations), as well as the different sources of (sometimes conflicting) optical data is analysed in detail. Specific interactions are considered for each projectile, such as electron capture/loss and electron cloud polarisation for ions, and indistinguishability, exchange and low-energy corrections for electrons. An estimate of possible contributions of surface excitations to the interaction probabilities of low energy electrons is given. Comparison of our results with a large collection of available experimental data shows good agreement. As a practical and useful outcome of the work, we provide analytical expressions fitting all our calculated quantities, which can be applied for simulation or comparison purposes.